Dosimetric comparison of Acuros XB, AAA, and XVMC in stereotactic body radiotherapy for lung cancer. Issue 8 (24th July 2014) - Tsuruta, Yusuke; Nakata, Manabu; Nakamura, Mitsuhiro; Matsuo, Yukinori; Higashimura, Kyoji; Monzen, Hajime; Mizowaki, Takashi; Hiraoka, Masahiro
Abstract : Purpose: To compare the dosimetric performance of Acuros XB (AXB), anisotropic analytical algorithm (AAA), and x‐ray voxel Monte Carlo (XVMC) in heterogeneous phantoms and lung stereotactic body radiotherapy (SBRT) plans. Methods: Water‐ and lung‐equivalent phantoms were combined to evaluate the percentage depth dose and dose profile. The radiation treatment machine Novalis (BrainLab AG, Feldkirchen, Germany) with an x‐ray beam energy of 6 MV was used to calculate the doses in the composite phantom at a source‐to‐surface distance of 100 cm with a gantry angle of 0°. Subsequently, the clinical lung SBRT plans for the 26 consecutive patients were transferred from the iPlan (ver. 4.1; BrainLab AG) to the Eclipse treatment planning systems (ver. 11.0.3; Varian Medical Systems, Palo Alto, CA). The doses were then recalculated with AXB and AAA while maintaining the XVMC‐calculated monitor units and beam arrangement. Then the dose‐volumetric data obtained using the three different radiation dose calculation algorithms were compared. Results: The results from AXB and XVMC agreed with measurements within ±3.0% for the lung‐equivalent phantom with a 6 × 6 cm 2 field size, whereas AAA values were higher than measurements in the heterogeneous zone and near the boundary, with the greatest difference being 4.1%. AXB and XVMC agreed well with measurements in terms of the profile shape at the boundary of the heterogeneous zone. For the lung SBRT plans, AXB yielded lower values than XVMC in terms of the maximum doses of ITV and PTV; however, the differences were within ±3.0%. In addition to the dose‐volumetric data, the dose distribution analysis showed that AXB yielded dose distribution calculations that were closer to those with XVMC than did AAA. Means ± standard deviation of the computation time was 221.6 ± 53.1 s (range, 124–358 s), 66.1 ± 16.0 s (range, 42–94 s), and 6.7 ± 1.1 s (range, 5–9 s) for XVMC, AXB, and AAA, respectively. Conclusions: In the phantom evaluations, AXB and XVMC agreed better with measurements than did AAA. Calculations differed in the density‐changing zones (substance boundaries) between AXB/XVMC and AAA. In the lung SBRT cases, a comparative analysis of dose‐volumetric data and dose distributions with XVMC demonstrated that the AXB provided better agreement with XVMC than AAA. The computation time of AXB was faster than that of XVMC; therefore, AXB has better balance in terms of the dosimetric performance and computation speed for clinical use than XVMC.